The Myeloid LSECtin Is a DAP12-Coupled Receptor That Is Crucial for Inflammatory Response Induced by Ebola Virus Glycoprotein. - Dianyuan Zhao; Xintao Han; Xuexing Zheng; Hualei Wang; Zaopeng Yang; Di Liu; Ke Han; Jing Liu; Xiaowen Wang; Wenting Yang; Qingyang Dong; Songtao Yang; et al. (PLoS Pathogens)
Fatal Ebola virus infection is characterized by a systemic inflammatory response similar to septic shock. Ebola glycoprotein (GP) is involved in this process through activating dendritic cells (DCs) and macrophages. However, the mechanism is unclear. Here, we showed that LSECtin (also known as CLEC4G) plays an important role in GP-mediated inflammatory responses in human DCs. Anti-LSECtin mAb engagement induced TNF-α and IL-6 production in DCs, whereas silencing of LSECtin abrogated this effect. Intriguingly, as a pathogen-derived ligand, Ebola GP could trigger TNF-α and IL-6 release by DCs through LSECtin. Mechanistic investigations revealed that LSECtin initiated signaling via association with a 12-kDa DNAX-activating protein (DAP12) and induced Syk activation. Mutation of key tyrosines in the DAP12 immunoreceptor tyrosine-based activation motif abrogated LSECtin-mediated signaling. Furthermore, Syk inhibitors significantly reduced the GP-triggered cytokine production in DCs. Therefore, our results demonstrate that LSECtin is required for the GP-induced inflammatory response, providing new insights into the EBOV-mediated inflammatory response.